(untitled) (Research, Society and Development, 2023)
Imaging diagnostic methods such as mammography, ultrasound and scintigraphy are essential exams in the diagnosis of breast cancer, screening and monitoring. However, they all have specific limitations. In 1990, the mammography committee of the Colégio Brasileiro de Radiologia e Diagnóstico por Imagem (CBR) was created, in which companies began to improve the quality of mammography machines, and physicists began to control the quality of mammography. With this, a new issue came to light, that of interpreting doctors. The BI-RADS reporting system then emerged, which represented a notable improvement in the standardization of language and interpretation of mammograms. Early detection of breast cancer is the crucial element, therefore, programs are carried out to detect breast cancer early. For the Brazilian Society of Mastology, the ideal age is 40 years, while for the Ministry of Health it is 50 years. In this work, the authors carried out a narrative bibliographic review, which describes the indications and findings of magnetic resonance imaging in breast cancer, as well as the role of mammography, its impacts, advantages, limitations and its use for screening breast lesions, the same also explores in detail the fundamental role of radiology in the comprehensive management of breast cancer, highlighting its transformative potential in promoting women’s health around the world.